Patterns of renal dopamine release to regulate diuresis and natriuresis during volume expansion: role of renal monoamine-oxidase - De Luca Sarobe, Verónica (2010)
Diuretic and natriuretic effects of renal dopamine (DA) are well established. However, in volume expansion the pattern of renal DA release into urine (UDAV) and the role of enzymes involved in DA synthesis/degradation have not yet been defined. The objective was to determine the pattern of UDAV during volume expansion and to characterize the involvement of monoamine-oxidase (MAO) and aromatic amino-acid decarboxylase (AADC) in this response. In this study male Wistar rats were expanded with NaCl 0.9% at a rate of 5% BWt per hour. At the beginning of expansion three groups received a single drug injection as follows: C (vehicle, Control), IMAO (MAO inhibitor Pargyline, 20 mg/kg BWt, i.v.) and BNZ (AADC inhibitor Benserazide, 25 mg/kg BWt, i.v.). Results revealed that in C rats UDAV (ng/30 min/100g BWt) increased in the first 30 min expansion from 11.5 ± 1.20 to 21.8 ± 3.10 (p < 0.05) and decreased thereafter. IMAO showed a similar pattern but significantly higher than C at 30 min expansion (32.5 ± 2.20, p < 0.05). IMAO greatly reduced MAO activity from 8.29 ± 0.35 to 1.1 ± 0.03 nmol/mg tissue/hour and significantly increased diuresis and natriuresis over controls. BNZ abolished the early UDAV peak to 3.2±0.72 (p < 0.01) and though, UDAV increased over C after 60 min expansion, natriuresis and diuresis were diminished by BNZ treatment. Results indicate that an increment in renal DA release into urine occurs early in expansion and in a peak-shaped way. In this response MAO plays a predominant role.